Exploring Mixed Materials in Creating Peony Flower Embellishments on Party Dress - Audina Nur Saffanah; Mandhe Sekar Nurindah (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2026)
This research explores the use of mixed materials in creating Peony flower embellishments for party wear using the Double Diamond Model (discover, define, develop, deliver). The Peony’s layered and wavy morphology is translated through combinations of satin, chiffon, organza, tulle, and cotton, applying cutting, burning, and layering techniques to achieve dimensional effects. The results show that the combination of satin and organza with full petal patterns and the combination of cotton and chiffon with intersecting petal patterns most effectively represent Peony characteristics, while sequins enhance visual value. This study contributes a practical framework for translating complex floral forms through specific fabric combinations and material manipulation techniques. The findings suggest that this mixed material approach can support the development of more innovative and aesthetically refined party wear.